Ui/Ux Design For Progressive Tax Payment And Vehicle Blocking Services Website Using The Ideo Method - Sri Wahyuni; Tasril, Virdyra; Muhammad Iqbal (ENCRYPTION: Journal of Information And Technology, 2024)
This research aims to design the user interface (UI) and user experience (UX) for a website providing progressive tax payment and vehicle blocking services using the IDEO method. The IDEO method consists of 3 main stages: Inspiration, Ideation, and Implementation. In the Inspiration stage, observations and interviews were conducted to identify user problems and needs related to these services. The Ideation stage involved brainstorming and creating sketches/wireframes to generate appropriate UI/UX design concepts. The results show that the developed website UI/UX design was able to improve the ease of use, efficiency, and user satisfaction in accessing the services. Key features implemented include an intuitive dashboard, a simple and transparent progressive tax payment flow, a digital assistant feature, integration with digital payment systems, and a responsive design. Testing using the System Usability Scale (SUS) resulted in a score of 74.736, indicating that this website UI/UX design is in the "acceptable" category the design is quite good and acceptable to users.